2018
DOI: 10.1186/s40623-018-0880-y
|View full text |Cite
|
Sign up to set email alerts
|

Lateral variation of the uppermost oceanic plate in the outer-rise region of the Northwest Pacific Ocean inferred from Po-to-s converted waves

Abstract: The uppermost structures of incoming oceanic plates have been investigated by seismic exploration surveys, primarily based on two-dimensional profiles. However, their regional-scale lateral variations and shear wave velocity structures with higher-frequency components remain elusive. This study, using passive seismic records, attempted to retrieve Po-to-s converted waves (Pos) by cross-correlating Po wave coda from the radial and vertical components in the 2-6 Hz frequency band and to show lateral variations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…(2014). Based on a 2‐D FDM simulation with a finer (0.02 km) grid, we confirmed that such a thin layer has only a minor effect on Po/So propagation, especially for Z component, though it may cause large Po ‐to‐ S conversion at the seafloor for R motion (Tonegawa et al., 2018, see, Figure S2 in Supporting Information).…”
Section: ‐D Fdm Simulationsupporting
confidence: 69%
“…(2014). Based on a 2‐D FDM simulation with a finer (0.02 km) grid, we confirmed that such a thin layer has only a minor effect on Po/So propagation, especially for Z component, though it may cause large Po ‐to‐ S conversion at the seafloor for R motion (Tonegawa et al., 2018, see, Figure S2 in Supporting Information).…”
Section: ‐D Fdm Simulationsupporting
confidence: 69%
“…Although we could not constrain the mantle velocity structure well, seismic velocities in the uppermost mantle could be low (V p < 8.0 km/s) near petit-spot volcanoes ( Figure S4), and we imaged an unclear or absent Moho reflection in the distance range from 55 to 80 km on the MCS reflection section (Figure 2). Furthermore, Tonegawa et al (2018) also reported a weakened or absent interface at the crust-mantle boundary near the same petit-spot. Therefore, ascending magma associated with petit-spot volcanic activity may modify not only the shallower part of the oceanic crust but also the crust-mantle boundary.…”
Section: Geophysical Research Lettersmentioning
confidence: 83%
“…Specifically, the reduced crustal velocity below the basement can be explained by fractures and hydration associated with petit-spot volcanic activity. In their analysis of passive seismic records, Tonegawa et al (2018) used Pos waves to image the basement and oceanic Moho in the outer-rise region of the Japan and Kuril trenches. They imaged a clear basement and oceanic Moho in seaward regions, whereas they obtained weakened or no Pos waves near the trench.…”
Section: Geophysical Research Lettersmentioning
confidence: 99%
See 1 more Smart Citation
“…The RFs were calculated through a spectral division of the radial components by the vertical components with a water level of 0.001 (e.g., Langston 1977Langston , 1979. We used a time window from − 2 to 3 s from the picked P arrival times in the vertical component to avoid contamination of water reverberation in the deconvolution (Tonegawa et al 2018) and applied a cosine taper of 10% of the time window. The time window of the radial component was from − 2 s to 14 s from the picked P arrival times.…”
Section: Rf Analysesmentioning
confidence: 99%